ORGANIZATIONAL DIVERSITY: PERSPECTIVE NEED FOR COGNITION, ORGANIZATIONAL SUPPORT, AND ORGANIZATION CULTURE STUDY IN THE INDONESIAN Z GENERATION - Ferrynela Purbo Laksono; Albertus Yudi Yuniarto; Nicko Kornelius Putra (SEAN Institute, 2023)
Various studies on issues of diversity have been carried out. This study is related to diversity management (Mazur, 2014). López et al (2019) research linking culture organizations to diversity. Innovative culture can increase respect for diversity. Cole et al., (2018) found identity to be the key to organizational behavior. Identity issues can determine the response of organizational members. Hsiao et al., (2015) found that diversity determines the behavior of individuals in organizations. These various studies indicate that the topic of diversity still requires further research Diversity is a complex issue in many aspects. Organizations also experience many diversity problems. The research wants to know the Zer generation’s perception of organizational diversity, perceived organizational support, organizational culture, and need for cognition. The study aimed to examine the influence of perceived organizational support, organizational culture, and the need for cognition on organizational diversity. The sample of this research is the Zer generation throughout Indonesia. The total sample collected is 335 respondents. The analysis uses Multiple Regression. Analysis tool using SPSS. This study's findings show that simultaneity influences perceived organizational support, organizational culture, and the need for cognition of diversity. Although, the findings partially show there is no influence between perceived organization support and diversity. On the other side, there is an influence between organizational culture and the need for cognition of diversity.